Warrior for Clean Skies: Anti-Geoengineering Activist Rosalind Peterson’s Environmental Legacy - Williams, Rob (Advances in Social Sciences Research Journal, 2020)
US citizen scientist, researcher, and anti-geoengineering activist Rosalind Peterson of Mendocino, California, proved both pioneer and prophet. She helped catalyze a global grassroots anti-geoengineering movement through her decades-long work crusading for clearer skies, cleaner water, healthier trees and plants, and a more resilient planet free of geoengineering fallout. Peterson combined scientific data collection and research, publishing, public speaking, and political advocacy to educate the world about the many negative environmental consequences of clandestine geoengineering. In 2002 Peterson founded California Skywatch (CSW), and in 2006 the Agricultural Defense Coalition (ADC). The two organizations merged in January 2011 and remain vital online public repositories of scientific data, legislative documents, and visual evidence of covert geoengineering programs. Peterson’s indefatigable efforts over three decades to call global public attention to the environmental consequences of geoengineering exemplify the potential power of the citizen scientist to shape scientific and political processes and outcomes. Peterson’s decades-long effort to uncover the myriad toxic environmental impacts of clandestine geoengineering also provides a compelling, scientifically researched alternative to the widely accepted theory advanced by the United Nations’ Intergovernmental Panel on Climate Change (IPCC) that global warming is primarily caused by anthropogenically released carbon dioxide.